Verification of safety critical and control systems of Nuclear Power Plants using Petri nets - Singh P.; Singh L. (My University, 2025)
Non-functional requirements play a critical role in designing variety of applications domain ranging from safety-critical systems to simple gaming applications. Performance is one of the crucial non-functional requirements, especially in control and safety systems, which validates the design. System risk can be quantified as a product of probability of system failure and severity of its impact. In this paper, we devise a technique to do the performance analysis of safety critical and control systems that helps to estimate the risk. The technique elaborates Petri nets to estimate performability to ensure system dependability requirements. We illustrate the technique on a case study of Nuclear Power Plant. The technique has been validated on its 17 safety critical and control systems. © 2019 Elsevier Ltd